Hydrogen Limitation and Syntrophic Growth among Natural Assemblages of Thermophilic Methanogens at Deep-sea Hydrothermal Vents - Topçuoğlu, Begüm D.; Stewart, Lucy C.; Morrison, Hilary G.; Butterfield, David A.; Huber, Julie A.; Holden, James F. (Frontiers in Microbiology, 2016)
Thermophilic methanogens are common autotrophs at hydrothermal vents, but their growth constraints and dependence on H2 syntrophy in situ are poorly understood. Between 2012 and 2015, methanogens and H2-producing heterotrophs were detected by growth at 80°C and 55°C at most diffuse (7-40°C) hydrothermal vent sites at Axial Seamount. Microcosm incubations of diffuse hydrothermal fluids at 80°C and 55°C demonstrated that growth of thermophilic and hyperthermophilic methanogens is primarily limited by H2 availability. Amendment of microcosms with NH4+ generally had no effect on CH4 production. However, annual variations in abundance and CH4 production were observed in relation to the eruption cycle of the seamount. Microcosm incubations of hydrothermal fluids at 80°C and 55°C supplemented with tryptone and no added H2 showed CH4 production indicating the capacity in situ for methanogenic H2 syntrophy. 16S rRNA genes were found in 80°C microcosms from H2-producing archaea and H2-consuming methanogens, but not for any bacteria. In 55°C microcosms, sequences were found from the H2-producing bacteria and H2-consuming methanogens and sulfate-reducing bacteria. A co-culture of representative organisms showed that Thermococcus paralvinellae supported the syntrophic growth of Methanocaldococcus bathoardescens at 82°C and Methanothermococcus sp. strain BW11 at 60°C. The results demonstrate that modeling of subseafloor methanogenesis should focus primarily on H2 availability and temperature, and that thermophilic H2 syntrophy can support methanogenesis within natural microbial assemblages and may be an important energy source for thermophilic autotrophs in marine geothermal environments.